Neutralizing Antibody Induction Associated with a Germline Immunoglobulin Gene Polymorphism in Neutralization-Resistant SIVsmE543-3 Infection - Yuto Nomura; Saori Matsuoka; Midori Okazaki; Takeo Kuwata; Tetsuro Matano; Hiroshi Ishii (Viruses, 2021)
Antibody responses are crucial for the control of virus infection. Understanding of the mechanism of antibody induction is important for the development of a vaccine eliciting effective anti-virus antibodies. Virus-specific B cell receptor (BCR)/antibody repertoires are different among individuals, but determinants for this difference remain largely unclear. We have recently reported that a germline BCR immunoglobulin (IgG) gene polymorphism (VH3.33_ET or VH3.33_VI) in rhesus macaques is the determinant for induction of potent B404-class anti-simian immunodeficiency virus (SIV) neutralizing antibodies in neutralization-sensitive SIVsmH635FC infection. In the present study, we examined whether neutralization-resistant SIVsmE543-3 infection can induce the anti-SIV neutralizing antibodies associated with the germline VH3.33 polymorphism. Anti-SIVsmE543-3 neutralizing antibodies were induced in all the macaques possessing the VH3.33_ET allele, but not in those without VH3.33_ET, in the chronic phase of SIVsmE543-3 infection. Next generation sequencing analysis of BCR VH genes found B404-class antibody sequences only in those with VH3.33_ET. These results indicate that anti-SIVsmE543-3 neutralizing antibody induction associated with the germline BCR IgG gene polymorphism can be triggered by infection with neutralization-resistant SIVsmE543-3. This animal model would be useful for the elucidation of the mechanism of potent antibody induction against neutralization-resistant viruses.